ENHANCING CRITICAL THINKING THROUGH DEBATE TECHNIQUE - Hanafi Wibowo; Zharifah Nasroh Azizah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
This research based on the important of the student’s critical thinking for general students. Critical thinking is very important in daily life. Because , students are required to have the ability to choose and sort the information that is good and true. This research to identify how far debate can effect student’s critical thinking. This research was classroom action research it consist of two cycle, each cycle consist of three meetings. The data had been taken from each cycle then the average is compared. If there is an enhance in this research it means the research is successful. But if there is no enhance in this research it means the research is failed. This research is conducted in Islamic University Of Assyafi’iyah, It was located in Jatiwaringin street. This research was involved the first Semester English Education Study Program was consist of 34 college students and they were as subjects of this research. This research was considered successful by researchers because there was a significant improvement from cycle one to cycle two, which 62,87 to 70,37. The results of this research help teachers to enhance students’ critical thinking through debate technique.